2017
DOI: 10.1002/adv.21928
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid–agave fiber biocomposites produced by rotational molding: A comparative study with compression molding

Abstract: In this work, the possibility to produce polylactic acid (PLA) and agave fiber biocomposites by dry-blending and rotational molding was studied. The samples were also produced by compression molding to compare the effect of processing conditions on the biocomposites properties. In particular, the effect of fiber content (0-40 wt.%) on morphology, density, porosity, thermal (DSC) and mechanical properties (tension, flexion, impact and hardness) was studied. Also, a complete analysis of the internal air temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 43 publications
3
37
1
Order By: Relevance
“…This result indicates that the lignocellulosic fillers induced a nucleating effect that favored the formation of crystals in the green composites. In the case of the lower X C_max values for the green composites containing 40 wt% and 50 wt% of TCHF, one can consider that the fillers presence at these contents also supposed an obstacle for the biopolymer chains to form stable crystals, generating a negative effect on crystallinity and leading to the formation of a more amorphous structure [66][67][68]. Furthermore, one can also observe that the torrefaction process did not yield any significant effect on the thermal properties of PLA at the studied filler loading, suggesting that nucleation was based on a physical phenomenon.…”
Section: Thermal Performance Of the Green Composite Piecesmentioning
confidence: 99%
“…This result indicates that the lignocellulosic fillers induced a nucleating effect that favored the formation of crystals in the green composites. In the case of the lower X C_max values for the green composites containing 40 wt% and 50 wt% of TCHF, one can consider that the fillers presence at these contents also supposed an obstacle for the biopolymer chains to form stable crystals, generating a negative effect on crystallinity and leading to the formation of a more amorphous structure [66][67][68]. Furthermore, one can also observe that the torrefaction process did not yield any significant effect on the thermal properties of PLA at the studied filler loading, suggesting that nucleation was based on a physical phenomenon.…”
Section: Thermal Performance Of the Green Composite Piecesmentioning
confidence: 99%
“…Other authors, working with Agave tequilana fibres [33], also found that, for compression moulding and PP composites, 30% of fibre provides the best mechanical results. Cisneros-López and collaborators [41] found that rotationally moulded PLA composites with 10% of agave fibres (agave tequilana) does not change elastic modulus, while higher fibre ratios lead to the reduction of this property; on the other hand, compression moulded PLA allowed increasing the elastic modulus of net PLA by a 14% for 30% composites, while 40% fibre composites had an elastic modulus 13% lower. These authors obtained also similar results for flexural properties, that is, mechanical properties remained unchanged for 10% composites, while drastic reductions were observed for 40% composites.…”
Section: Composites Characterizationmentioning
confidence: 99%
“…Different polymer processing technologies, such as extrusion, injection molding, calendering, thermoforming, and fiber spinning [1,2], have been properly adapted to the production of different PLA items. On the other hand, PLA has been shown to be a very attractive polymer for the production of hollow articles by rotational molding [3,4]. The most relevant application, allowed by the use of PLA for rotomolding, lies in the possibility of producing a new class of eco-friendly hollow objects (e.g., pots or containers), which can be easily discarded after their usage due to the material biodegradability [5].…”
Section: Introductionmentioning
confidence: 99%